Measurement of the average lifetime of b-hadrons in Z decays - Acciarri, M; Adriani, O; Aguilar-Benitez, M; Ahlen, S; Alcaraz, J; Alemanni, G; Allaby, J; Aloisio, A; Alverson, G; Alviggi, MG; Ambrosi, G; Anderhub, H; et al. (1998)
We present a measurement of the average b-hadron lifetime τb at the e+e collider LEP. Using hadronic Z decays collected in the period from 1991 to 1994, two independent analyses have been performed. In the first one, the b-decay position is reconstructed as a secondary vertex of hadronic b-decay particles. The second analysis is an updated measurement of Tb using the impact parameter of leptons with high momentum and high transverse momentum. The combined result is τb = [1549 ± 9 (stat) ± 15 (syst)] fs. In addition, we measure the average charged b-decay multiplicity 〈nb〉 and the normalized average b-energy 〈xE〉b at LEP to be 〈nb〉 = 4.90 ± 0.04 (stat) ± 0.11 (syst), 〈xE〉b = 0.709 ± 0.004 (stat + syst). © 1998 Published by Elsevier Science B.V.